Intranasal coinfection model allows for assessment of protein vaccines against nontypeableHaemophilus influenzaein mice. Issue 10 (October 2018) - Michel, Lea Vacca; Kaur, Ravinder; Zavorin, Mark; Pryharski, Karin; Khan, Nadeem M.; LaClair, Ciara; O'Neil, Meghan; Xu, Qingfu; Pichichero, Michael E.
Abstract : Purpose. : Nontypeable Haemophilus influenzae (NTHi) is a commensal in the human nasopharynx and the cause of pneumonia, meningitis, sinusitis, acute exacerbations of chronic obstructive pulmonary disease and acute otitis media (AOM). AOM is the most common ailment for which antibiotics are prescribed in the United States. With the emergence of new strains of antibiotic‐resistant bacteria, finding an effective and broad coverage vaccine to protect against AOM‐causing pathogens has become a priority. Mouse models are a cost‐effective and efficient way to help determine vaccine efficacy. Here, we describe an NTHi AOM model in C57BL/6J mice, which also utilizes a mouse‐adapted H1N1 influenza virus to mimic human coinfection. Methodology. : We tested our coinfection model using a protein vaccine formulation containing protein D, a well‐studied NTHi vaccine candidate that can be found in the 10‐valent Streptococcus pneumoniae conjugate vaccine. We verified the usefulness of our mouse model by comparing bacterial loads in the nose and ear between protein D‐vaccinated and control mice. Results. : While there was no measurable difference in nasal bacterial loads, we did detect significant differences in the bacterial loads of ear washes and ear bullae between vaccinated and control mice. Conclusion. : The results from this study suggest that our NTHi AOM coinfection model is useful for assessing protein vaccines.